So what are we really talking about? A Corpus Linguistic Analysis of Keywords and Collocations in the »Theologische Quartalsschrift« - Matthias Werner (Warszawskie Studia Teologiczne)
This article presents a corpus linguistic analysis of the »Theologische Quartalsschrift«, a German journal on theology. The research identifies topics discussed in Catholic Theology by analyzing 81 volumes from 1925 to 2006 (excluding 1945). By filtering the corpus and focusing on nouns, frequent terms are identified, offering insights into central subjects. The study enhances understanding of German Catholic Theology, providing transparency and objective insights in order to provide a clear explanation of Catholic Theology to outsiders, even in secularized contexts. To insiders, this approach enables the discovery of blind spots and fosters discourse in scientific theology by making discussions explicit. Overall, it demonstrates the usefulness of corpus linguistics in studying theological discourse and sheds light on the topics theologians engage with. The analysis contributes to a more informed and constructive dialogue within the field.